Genetic analysis of impaired trimethylamine metabolism using whole exome sequencing. Issue 1 (December 2017) - Guo, Yiran; Hwang, Liang-Dar; Li, Jiankang; Eades, Jason; Yu, Chung; Mansfield, Corrine; Burdick-Will, Alexis; Chang, Xiao; Chen, Yulan; Duke, Fujiko; Zhang, Jianguo; Fakharzadeh, Steven; et al.
Abstract Background Trimethylaminuria (TMAU) is a genetic disorder whereby people cannot convert trimethylamine (TMA) to its oxidized form (TMAO), a process that requires the liver enzyme FMO3. Loss-of-function variants in theFMO3 gene are a known cause of TMAU. In addition to the inability to metabolize TMA precursors like choline, patients often emit a characteristic odor because while TMAO is odorless, TMA has a fishy smell. The Monell Chemical Senses Center is a research institute with a program to evaluate people with odor complaints for TMAU. Methods Here we evaluated ten subjects by (1) odor evaluation by a trained sensory panel, (2) analysis of their urine concentration of TMA relative to TMAO before and after choline ingestion, and (3) whole exome sequencing as well as subsequent variant analysis of all ten samples to investigate the genetics of TMAU. Results While all subjects reported they often emitted a fish-like odor, none had this malodor during sensory evaluation. However, all were impaired in their ability to produce >90% TMAO/TMA in their urine and thus met the criteria for TMAU. To probe for genetic causes, the exome of each subject was sequenced, and variants were filtered by genes with a known (FMO3 ) or expected effect on TMA metabolism function (other oxidoreductases). We filtered the remaining variants by allele frequency and predicated functional effects. We identified one subject that had a rare loss-of-functionFMO3 variant and six with more common decreased-function variants. In other oxidoreductases genes, five subjects had four novel rare single-nucleotide polymorphisms as well as one rare insertion/deletion. Novel in this context means no investigators have previously linked these variants to TMAU although they are in dbSNP. Conclusions Thus, variants in genes other thanFMO3 may cause TMAU and the genetic variants identified here serve as a starting point for future studies of impaired TMA metabolism.